2022
DOI: 10.3389/fgene.2022.765502
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Interaction Study of Late-Onset Asthma With Seven Environmental Factors Using a Structured Linear Mixed Model in Europeans

Abstract: Asthma is among the most common chronic diseases worldwide, creating a substantial healthcare burden. In late-onset asthma, there are wide global differences in asthma prevalence and low genetic heritability. It has been suggested as evidence for genetic susceptibility to asthma triggered by exposure to multiple environmental factors. Very few genome-wide interaction studies have identified gene-environment (G×E) interaction loci for asthma in adults. We evaluated genetic loci for late-onset asthma showing G×E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…It is furthed identified that SIK2 and SIK3 play essential roles in producing inflammatory mediators that trigger airway inflammation, suggesting inhibitors of these protein kinases may have therapeutic potential for the treatment of mast cell‐driven diseases, such as asthma (Darling et al, 2021). Other RRS genes including CPS1, HSPA7, TXNL4B and PARD6A have also been shown to be linked with asthma (Baek et al, 2022; Shevchenko et al, 2020; Tougan et al, 2008). We would like to point out that the current manuscript can be viewed as an extension to our previous work (Cao et al, 2022), which focused solely on the development of RNA‐seq risk score.…”
Section: Discussionmentioning
confidence: 99%
“…It is furthed identified that SIK2 and SIK3 play essential roles in producing inflammatory mediators that trigger airway inflammation, suggesting inhibitors of these protein kinases may have therapeutic potential for the treatment of mast cell‐driven diseases, such as asthma (Darling et al, 2021). Other RRS genes including CPS1, HSPA7, TXNL4B and PARD6A have also been shown to be linked with asthma (Baek et al, 2022; Shevchenko et al, 2020; Tougan et al, 2008). We would like to point out that the current manuscript can be viewed as an extension to our previous work (Cao et al, 2022), which focused solely on the development of RNA‐seq risk score.…”
Section: Discussionmentioning
confidence: 99%
“…We further performed age-specific stratified analyses both in PWH and HIV-negative counterparts. The genome-wide significance threshold was considered at P value less than 5 × 10 -8 , and P value less than 1 × 10 -6 indicated a suggestive significance threshold [27,28]. Plots of representative SNPs were generated using LocusZoom online software [29].…”
Section: Genome-wide Association (Gwa) Analysesmentioning
confidence: 99%